The effects of boardroom gender diversity and audit quality on financial earnings smoothing in GCC countries: Do government board members moderate the relationship? - Alsmady, Ahnaf Ali (Asian Journal of Economic Modelling, 2023)
This study explores the effects of boardroom gender and audit quality on financial earnings smoothing (FES) in the Gulf Cooperation Council (GCC) countries. Additionally, the moderating effects of government representatives as board members on FES are investigated. The study covers six GCC countries: Saudi Arabia, the UAE, Oman, Bahrain, Kuwait, and Qatar. The sample comprises 188 firms from 2013 to 2019. Multiple regression models are used to evaluate the study’s hypotheses. The findings show that the big international and local firms that have both female and male board members, as well as government representatives, on their boards demonstrate effective governance mechanisms. Although they had a negative impact on higher FES, they had a positive impact on lower FES. As for the moderating role, the findings reveal that the role of government members on the board is complementary to the audit quality, particularly in the big four international and local firms. This research may aid businesses in implementing the best governance practices to avoid FES and improve the quality of accounting data, in line with the objectives of the government. However, good practices in moderating earnings smoothing were mainly seen amongst the males.